Postharvest Handling Of Coffee In Small Medium Enterprises (SMEs) Tugu Juang Coffee, Pulosari Village, Pemalang Regency - Sari Salsabila Rizkiyani; Yan El Rizal Unzilatirrizqi (Program Studi Ilmu Teknologi Pangan Universitas Muhadi Setiabudi, 2021)
This study aims to determine the entire postharvest processing of coffee at Small Medium Enterprises (SMEs) Tugu Juang Coffee in Pulosari Village, Pulosari District, Pemalang Regency. The types of coffee that are cultivated and processed are robusta and arabica coffee. The research method used is observation, interview, and documentation study. The coffee processing process at Small Medium Enterprises (SMEs) Tugu Juang Coffeeis the dry (natural) processing process that starts from picking, sorting the coffee fruit, drying, peeling dry skin, roasting, resting, pulping and packaging. The water content before drying reaches 25-30% and after drying it produces a maximum moisture content of 12%. The warehousing process at Small Medium Enterprises (SMEs) Tugu Juang Coffee always maintains clean sacks, ventilation and labeling